2016
DOI: 10.1063/1.4964716
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of immune and cancer cell interactions at single cell level in microfluidic droplets

Abstract: Cell-cell communication mediates immune responses to physiological stimuli at local and systemic levels. Intercellular communication occurs via a direct contact between cells as well as by secretory contact-independent mechanisms. However, there are few existing methods that allow quantitative resolution of contact-dependent and independent cellular processes in a rapid, precisely controlled, and dynamic format. This study utilizes a high-throughput microfluidic droplet array platform to analyze cell-cell inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 62 publications
0
61
0
Order By: Relevance
“…For instance, only about 20%-25% of patients respond to immuno-oncology drugs (Dempke et al, 2017;Schumacher et al, 2015). This limited response rate is likely because of the complex network of cell-cell interactions present in a tumor microenvironment, our knowledge of which is still incomplete (Sarkar et al, 2016). To better stratify patients for existing therapies as well as to discover interactions that could be targeted, there is a need to more fully understand the spectrum of cell-cell interactions occurring in tumor microenvironments and how these interactions affect outcome.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, only about 20%-25% of patients respond to immuno-oncology drugs (Dempke et al, 2017;Schumacher et al, 2015). This limited response rate is likely because of the complex network of cell-cell interactions present in a tumor microenvironment, our knowledge of which is still incomplete (Sarkar et al, 2016). To better stratify patients for existing therapies as well as to discover interactions that could be targeted, there is a need to more fully understand the spectrum of cell-cell interactions occurring in tumor microenvironments and how these interactions affect outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it can integrate real-time cytokine profiling by bead-based cytokine sensors [80] or gene expression profiling by single cell retrieval via micromanipulator [81] due to the non-destructive feature of this assay. Similarly, it has also been reported that droplets can be used to co-encapsulate the two types of cells before docking to the microwells [82]. This microwell-based device was compatible with live cell imaging analysis, allowing the dynamic monitoring of cell morphology, behavior, and fate.…”
Section: Integrated Platforms To Monitor Dynamic T-cell Behavior and mentioning
confidence: 90%
“…C) Droplet‐assisted cell contacts and tumor defeat observation: i) droplets generation on the microchamber chip; ii) time lapse images of DC–T cells interaction in the T‐cell activation process. Reproduced with permission . Copyright 2016, AIP Publishing.…”
Section: Immunotherapy Studies On Microfluidic Chipsmentioning
confidence: 99%
“…Other than the sedimentation of cell suspension, cell encapsulation, which is induced by droplet formation, is also helpful for cell loading into the microchambers. Konry and co‐workers trapped T cells along with immature/mature DCs in hydrogel droplets to study T cells' activation (see Figure C). The result showed that mature DCs exhibited higher contact frequency and extended contact period during T‐cell activation process.…”
Section: Immunotherapy Studies On Microfluidic Chipsmentioning
confidence: 99%